2000
DOI: 10.1093/brain/123.12.2423
|View full text |Cite
|
Sign up to set email alerts
|

Brain iron deposition in Parkinson's disease imaged using the PRIME magnetic resonance sequence

Abstract: Iron content of the basal ganglia was investigated in 25 patients with idiopathic Parkinson's disease and 14 matched healthy control subjects using a partially refocused interleaved multiple echo sequence on a 1.5 Tesla MRI system. R(2)* (1/T(2)*) and R(2)' (1/T(2)') relaxation rates were higher in the substantia nigra of patients with Parkinson's disease, which indicates that iron content is elevated in this region. R(2)' was lower in the putamen, indicating reduced iron levels; reduction in this region was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
186
0
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(213 citation statements)
references
References 44 publications
21
186
0
6
Order By: Relevance
“…Target Organ-Although MRI is most often used to estimate cardiac and hepatic iron, MRI can also been used to characterize tissue iron deposits in the brain, pituitary gland, bone marrow, kidney and pancreas (36)(37)(38)(39)(40)(41)(42). These approaches observe the same physical principles as cardiac and hepatic iron imaging but present different imaging challenges.…”
Section: Choice Of Field Strength-mostmentioning
confidence: 99%
See 1 more Smart Citation
“…Target Organ-Although MRI is most often used to estimate cardiac and hepatic iron, MRI can also been used to characterize tissue iron deposits in the brain, pituitary gland, bone marrow, kidney and pancreas (36)(37)(38)(39)(40)(41)(42). These approaches observe the same physical principles as cardiac and hepatic iron imaging but present different imaging challenges.…”
Section: Choice Of Field Strength-mostmentioning
confidence: 99%
“…In contrast, splenic iron deposits are quite large and spin-echo (R2) techniques will not yield accurate iron estimates in this organ. The merits and limitations of these other techniques are beyond the scope of this manuscript, but several key references are included for interested readers (36)(37)(38)(39)(40)(41)(42).…”
Section: Choice Of Field Strength-mostmentioning
confidence: 99%
“…The R2' increase better reflects histological data that consistently demonstrates excessive iron deposition in the substantia nigra in PD. Other groups 33,38,41 have also shown that R2' estimates iron concentration more accurately than R2. Many other researchers 36,42,43 demonstrated that both R2 and R2' are affected by iron.…”
Section: Relaxometrymentioning
confidence: 99%
“…44 So in essence, R2 can be rendered somewhat insensitive by the water content in the brain, whereas R2* is susceptible to contributors other than iron, and R2' may have limited sensitivity. Sequences such as the gradient echo sampling of free induction decay and echo (GESFIDE) [45][46][47] and partially refocused interleaved multiple echo (PRIME) 38 allow the derivation of R2, R2*, and R2' from a single-pulse sequence. The GESFIDE sequence consists of two echo trains, the first after an excitation pulse, the second after a 180-degree refocusing pulse.…”
Section: Relaxometrymentioning
confidence: 99%
See 1 more Smart Citation